Using Guessing as A Word-Solving Strategy in Handling The Unknown Words to Improve Students' Vocabulary Interpretation of A Text - Sofia Maurisa (Universitas Negeri Malang, 2013)
This Classroom Action Research is conducted to implement the strategy of guessing to solve the students' vocabulary interpretation problem of inferring and handling unknown words which, in turn, improves their overall performance in vocabulary course. It is conducted in a cycle consisting of four meetings. The cycle is ended with one final meeting for vocabulary teacher-made test. Field notes, questionnaires, and a vocabulary test are used to collect the data. The result of the study revealed that the clear and applicable procedures of guessing strategy in handling the unknown words that consist of three major steps are: (1) drawing students' attention to cue words and phrases, (2) using leading questions to direct student in step-by-step search for and use of context clues, and (3) preparing vocabulary exercise allowing students to make inference and explain the process of guessing, could improve students' skills in vocabulary interpretation. The finding also shows that the guessing as a word-solving strategy is successful in drawing students' personal judgments or views toward its implementation. Students agreed that guessing as a word-solving strategy is a beneficial and easily-implemented strategy. They admitted that the strategy is comfortable to be used, and consider using it in the next vocabulary activities.  Key Words: vocabulary, unknown words, guessing strategy